CRH promotes S. pneumoniae growth in vitro and increases lung carriage in mice - Ndjom, Colette G. Ngo; Jones, Harlan P. (Frontiers in Microbiology, 2015)
Streptococcus pneumoniae (S. pneumoniae), a commensal across the nasal passages, is responsible for the majority of infectious pneumonia cases worldwide. Previous studies have shown that hormonal factors may be influential in regulating S. pneumoniae’s transition from a non-pathogen to a pathogenic state. The current study investigated the effects of corticotropin-releasing hormone (CRH), a peptide hormone involved in stress, on the pathogenicity of S. pneumoniae. Mice were infected with CRH-treated S. pneumoniae via intranasal route, showing an increase in pulmonary bacterial burden. We also quantified S. pneumoniae’s response to CRH through limited serial dilutions and growth curve analysis. We demonstrated that CRH promotes S. pneumoniae titer-dependent proliferation, as well as accelerates log-phase growth. Results also showed an increase in pneumococcal-associated virulence protein A virulence gene expression in response to CRH. These results demonstrate a role for CRH in Streptococcus pneumoniae pathogenicity, thus implicating CRH in mediating the transition of S. pneumoniae into a pathogenic state.